2009
DOI: 10.1111/j.1751-1097.2009.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Inactivation by Solar Ultraviolet Radiation Compared with Sensitivity to 254 nm Radiation

Abstract: Our goal was to derive a quantitative factor that would allow us to predict the solar sensitivity of vegetative bacterial cells to natural solar radiation from the wealth of data collected for cells exposed to UVC (254 nm) radiation. We constructed a solar effectiveness spectrum for inactivation of vegetative bacterial cells by combining the available action spectra for vegetative cell killing in the solar range with the natural sunlight spectrum that reaches the ground. We then analyzed previous studies repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 118 publications
(270 reference statements)
0
46
0
1
Order By: Relevance
“…Recent laboratory studies evaluating the kill effect of UV-C were conducted with single spores or close to single spore sizes on surfaces and in the air (Miller and Macher 2000;Ko et al 2002;Lin and Li 2002;Xu et al 2005;Foarde et al 2006;Menetrez 2006;Coohill and Sagripanti 2009;King et al 2011). However, by neglecting multispore clusters, little is known about the decay of potentially equally hazardous larger clusters such as those belonging to aerosols released by sneezing and coughing and other aerosols generated by crude or sophisticated methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recent laboratory studies evaluating the kill effect of UV-C were conducted with single spores or close to single spore sizes on surfaces and in the air (Miller and Macher 2000;Ko et al 2002;Lin and Li 2002;Xu et al 2005;Foarde et al 2006;Menetrez 2006;Coohill and Sagripanti 2009;King et al 2011). However, by neglecting multispore clusters, little is known about the decay of potentially equally hazardous larger clusters such as those belonging to aerosols released by sneezing and coughing and other aerosols generated by crude or sophisticated methods.…”
Section: Introductionmentioning
confidence: 99%
“…This higher rate of bacterial die-off in the spring than in the fall supports previous studies that have shown that survival of bacteria in soil is significantly greater at cooler temperatures (3,(20)(21)(22)(23). The differential survival is likely a function of ultraviolet radiation (UV), specifically, UV-B radiation (320 to 290 nm), as the UV-B radiation is the region of solar radiation responsible for the majority of bacterial cell death and is greater at warmer temperatures (24). In this study, both the average daily maximum temperature and UV-B radiation were significantly higher in the spring trial than in the fall.…”
Section: Discussionmentioning
confidence: 63%
“…UVB fractions of solar radiation around 300 nm have a biological impact, and the UV damage can generally extend to longer wavelengths and frequently occurs at UVA wavelengths also in bacteria (Coohill and Sagripanti 2009) and zooplankton (Copepoda; Kouwenberg et al 1999b). However, the biological impact on N. californicus eggs changed drastically at wavelengths between 300 and 310 nm, corresponding to the hatchability of T. urticae eggs (Sakai and Osakabe 2010).…”
Section: Discussionmentioning
confidence: 99%